SIGNATURES OF RIFT ENVIRONMENT IN THE PRODUCTION OF GARNET-AMPHIBOLITES AND ECLOGITES FROM TSO-MORARI REGION, LADAKH, INDIA: A GEOCHEMICAL STUDY - Rameshwar Rao D.; Hakim Rai (My University, 2006)
The geochemistry of eclogites and garnet-amphibolites from Tso-Morari region, Ladakh, India has been investigated to characterize their protoliths on the basis of immobile elements, especially trace elements including REE. The eclogites and garnet-amphibolites have coherent compositions, except for the UHP metamorphic minerals being preserved in eclogites. Compositionally, the metabasites range from 'depleted' to 'enriched', and span from within-plate basalts (WPB) to MORB fields, and match with various enriched or 'transitional' MORB types (e.g., on Ti-Zr-Y and Nb-Zr-Y ternary plots). Isotopically they have Sri ratio ~ 0.706 which is similar to some of the Ocean Island Basalt (OIB). The rocks under study suggest that the enriched components are probably derived by melting of a mantle source with an enriched OIB-type component rather than due to the crustal contamination. We propose a rift environment for their protoliths and relate to advanced intra-continental rift situation. Furthermore, our geochemical studies envisage an initial phase of plume activity (Cambrian or earlier) resulting in basaltic magma in the eclogitic layers at sub-lithospheric levels, wherein they were subjected to crystallization under ultra-high pressure conditions. At a later stage the reactivation of faults (probably during Permo-Triassic times) acted as channels for the emplacement of the high pressure rocks in the continental crust. Subsequently, the ultra-high pressure rocks got re-equilibrated as amphibolites, with some remaining as relict eclogites, which later got exposed to the surface during various phases of the Himalayan uplift. © 2006 Elsevier B.V. All rights reserved.
Keywords: ECLOGITES; GARNET-AMPHIBOLITES; LADAKH, INDIA; MANTLE PLUMES; TSO-MORARI CRYSTALLINE COMPLEX; Triassic; Cambrian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Cambrian; Палеозой::Кембрийская